W poszukiwaniu straconego Eleuzis. Szekspirowskie i indyjskie inspiracje w „Wampirze” Władysława Stanisława Reymonta - Kucab, Mateusz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The article is devoted to the less-known novel entitled “Vampire” by Władysław Stanisław Reymont, polish Nobel Prize Winner. It brings the subject of theatrical motifs and mechanism which have been used in the novel like dramatic dialogues and monologues, theatrum mundi theme. In the view of foregoing it has been proposed patters of subordination and guilt presented in the novel should be called the vampiric situations which is an appropriate term referring to relations between characters. The Vampire, alluding to William Shakespeare’s oeuvre (The Tempest in particular) and the culture of India, is another reflection of Reymont on the subject of great life’s celebration, searching for a place of one’s own in the world, articulating dreams and necessities.
Artykuł stanowi poszerzoną oraz znacznie zmodyfikowaną wersję referatu pt. Wyspa przebaczenia? ,,Burza” Williama Szekspira a ,,Wampir” Władysława Reymonta, który wygłosiłem na konferencji naukowej „Szekspir słowiański” zorganizowanej przez Polskie Towarzystwo Szekspirowskie. Konferencja odbyła się 20 listopada 2015 r. w Gdańskim Teatrze Szekspirowskim. W referacie przedstawiłem refleksję na temat związków Władysława Reymonta z dziełami Williama Szekspira. Zasadnicza oś tej refleksji pozostała niezmienna, ale większość tez, jak sądzę, wymagała weryfikacji i ponownego rozpatrzenia.
Keywords: Shakespearean and Indian motifs; theatrum mundi; Eleusis; novel; The Tempest; onirism